A High Prevalence Rate of a Positive Screen for Cognitive Impairment in Patients With Human Immunodeficiency Virus Attending an Irish Clinic. (27th December 2016) - McNamara, Patricia H.; Coen, Robert; Redmond, Janice; Doherty, Colin P.; Bergin, Colm
Abstract: Background: Human immunodeficiency virus (HIV)-associated neurocognitive disorders occurs in 20%–50% of HIV-positive patients. We undertook this study to assess the prevalence of a positive screen for cognitive impairment in the clinic population at our institution and to demonstrate the feasibility of implementing a screening program in routine clinical encounters. Methods: This was a cross-sectional study, and patients were recruited prospectively between December 2010 and February 2013. Inclusion criteria were as follows: patients were HIV positive, over the age of 18, capable of giving informed consent, and had sufficient ability to communicate in English. Patients were screened for cognitive impairment using the Brief Neurocognitive Screen. Results: A total of 604 patients were recruited, and 51.5% had a positive screen for cognitive impairment. The majority of the study cohort were male (78.8%), mean age was 40.9 (standard deviation, 10.2) years, 70.9% were Irish, the most common mode of transmission was men who have sex with men (49.3%), 83% were on antiretroviral therapy, and 88.7% were virally suppressed. Logistic regression showed that the main factors predictive of a positive screen for cognitive impairment were the endorsement of cognitive symptoms ( P = .024), being born in Africa ( P < .000001), the use of benzodiazepines ( P = .00341), being unemployed ( P = .008), and consumption of more than 40 units of alcohol weekly ( P = .035). There was a positive screen for depression in 9.1% and a positive screen for anxiety in 24.5%. Conclusions: The study highlights the necessity for a structured, prospective, large-scale screening program for cognitive impairment across countries with limited resources and demonstrates the feasibility of easily implementing this with minimal training.